Respostas
respondido por:
2
1 - (-1) = 1 + 1 = 2
3 - 1 = 2
ou
an = a1 + (n-1) r
3 = -1 + (3-1) r
3 + 1 = 2r
4 = 2r
r = 4:2
r = 2
3 - 1 = 2
ou
an = a1 + (n-1) r
3 = -1 + (3-1) r
3 + 1 = 2r
4 = 2r
r = 4:2
r = 2
jaifernandes1:
Muito obrigadaaaa ♥
respondido por:
0
Qual a razão da P.A: (-1,1,3...)
R = Razão
a1 = - 1
a2 = 1
FÓRMULA da RAZÃO
R = a2 - a1
R = 1 - (-1)
R = 1 + 1
R = 2 ( razão)
R = Razão
a1 = - 1
a2 = 1
FÓRMULA da RAZÃO
R = a2 - a1
R = 1 - (-1)
R = 1 + 1
R = 2 ( razão)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás